Entina HearSmart: a novel mobile based auditory training app for better adaptation of hearing aids - Navelkar, Rohan S.; Shukla, Radhika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The most common intervention prescribed for hearing impaired individuals is hearing aids. It has been noticed that in spite of using hearing aids, elderly individuals with hearing impairment, still struggle in hearing and understanding. Therefore, additional intervention is required for auditory rehabilitation to ease the adaptation of hearing aids. Evidence from studies published in the recent years suggests that, auditory training is likely a useful tool to improve speech perception and other cognitive skills in patients with hearing loss with and without the use of hearing aids. The aim of the study was to test the usefulness of our mobile app-based auditory training program to increase speech reception and communication and thereby improve hearing aid adaptability in patients with sensorineural hearing loss who have been fitted with a hearing aid. Methods: 40 patients were selected for the study, they were divided into 2 groups: Group 1 consisted of 20 patients who received auditory training using Entina HearSmart Android App, Group 2 consisted of 20 patients who received no auditory training (Control group). Results: The results showed that performance on the vowel, consonant and sentence tests in noise was significantly increased in patients who used our app for auditory training compared with that of the Non-Training Group. Conclusions: Entina HearSmart is a free, standardized and easy way to improve the outcome of hearing aids in adults and must be prescribed when a hearing aid has been fitted. When used sincerely after hearing aids have been fitted, using our app can significantly improve communication and thereby improve hearing aid adaptability.